The Ambivalence of Contemporary Islamic Philosophy Studies - Randa, Syafrinal; Hayati, Nur (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
Islamic philosophy is a critical study to answer the challenges of contemporary life. However, Islamic philosophy currently needs to improve its existence. Direction in the study of Islamic philosophy is essential, both in terms of methods and sources, so that the study of Islamic philosophy is not only in the world of new ideas but rather in existing realities. This article examines the challenges and innovations towards the ambivalence of Islamic philosophy in the contemporary era carried out by contemporary Indonesian Muslim philosophers. This article uses the library study method, which is a research approach carried out by collecting and analyzing information from written sources such as books, journals, articles, and documents related to the topic being discussed. This article finds that the importance of renewal in Islamic philosophical literacy is really needed as a guide for people who want to enter the world of Islamic philosophy with the study of living philosophy, as well as the digitalization of Islamic philosophy as a reflection that Islamic philosophy is fun.